PENDIDIKAN KARAKTER DISIPLIN DI SEKOLAH DASAR - Kristiyani (STKIP Subang, 2023)
The background to this research is the low cognitive learning outcomes in class V Natural and Social Sciences at SDN 1 Kendengsidialit. As many as 37% of students have achieved the Minimum Completeness Criteria (KKM). This is due to the lack of variation in the use of learning models and media. The formulation of the problem in this research is